2021
DOI: 10.1111/vsu.13694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of depth gauge accuracy in a canine tibial plateau leveling osteotomy model

Abstract: Objective To evaluate the accuracy of six depth gauges used in three tibial plateau leveling osteotomy (TPLO) plate holes. Study design Ex vivo experimental study. Animals and sample population Cadaveric canine limbs (n = 10), one 25‐mm‐thick wood board, and one 33.8‐mm‐diameter polyvinyl chloride (PVC) pipe. Methods A TPLO was performed on 10 canine cadaveric pelvic limbs. Three 3.5‐mm plate holes were filled with screws. The remaining three plate holes: a compression hole, a combination compression‐locking h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The choice of screw length in orthopedic surgery is most often based on post-drilling channel length measurements obtained using a depth gauge. This process can be very unreliable, with studies reporting average discrepancies between the measured and actual values of approximately 1 to 4 mm depending on the hole geometry and the type of depth gauge used [ 2 ]. Another study found that the rate of choosing an overly short screw or a screw which protruded more than 1 mm from the second cortex ranged from approximately 40 to 70% depending on the surgeon’s experience [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of screw length in orthopedic surgery is most often based on post-drilling channel length measurements obtained using a depth gauge. This process can be very unreliable, with studies reporting average discrepancies between the measured and actual values of approximately 1 to 4 mm depending on the hole geometry and the type of depth gauge used [ 2 ]. Another study found that the rate of choosing an overly short screw or a screw which protruded more than 1 mm from the second cortex ranged from approximately 40 to 70% depending on the surgeon’s experience [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Screw length determination is currently performed using a manual depth gauge, which typically consists of a calibrated rod hooked on one end that is manually inserted into the drilled hole to measure its depth. The measuring process is susceptible to human error and varies significantly depending on the surgeon’s experience, differences in technique [ 1 , 2 , 3 ], and differences in the manufacturer of the depth gauge [ 2 , 3 ]. This can prolong the duration of surgery [ 4 ] and lead to complications due to choosing a screw which is either too short or too long [ 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the parameters of the depth gauges in our study varied with each other. McChesney et al ( 22 ) mentioned that the amount of recess of the depth gauge base within a plate hole is influenced by the size and geometry of the depth gauge base and plate hole. A depth gauge with small-diameter base or long bevel may cause underestimate of the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, tactile feedback varies due to differences in cortical bone thickness and density at the metaphysis and diaphysis ( 21 ) resulting in measurement errors, which makes different passages of drilled holes another factor that influences measurement accuracy. A recent veterinary study also suggested that different depth gauges may affect the accuracy of the measurement ( 22 ).…”
Section: Introductionmentioning
confidence: 99%